2017
DOI: 10.1016/j.ajog.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for complete uterine rupture

Abstract: Sequential labor induction with prostaglandins and oxytocin and augmentation of labor with oxytocin are important risk factors for complete uterine rupture in intact and scarred uteri.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 18 publications
(20 reference statements)
5
70
2
1
Order By: Relevance
“…Another important finding is the clear pattern of increased odds of UR with increasing parity after controlling for covariates. Other authors have found an increase in UR with higher parity [ 3 , 7 , 9 ]. For example, a study examining risk of complete UR in Norway found women (without a previous cesarean delivery) with a parity of three or more had 2.4 greater odds of complete UR compared to women with less than three births [ 7 ].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Another important finding is the clear pattern of increased odds of UR with increasing parity after controlling for covariates. Other authors have found an increase in UR with higher parity [ 3 , 7 , 9 ]. For example, a study examining risk of complete UR in Norway found women (without a previous cesarean delivery) with a parity of three or more had 2.4 greater odds of complete UR compared to women with less than three births [ 7 ].…”
Section: Discussionmentioning
confidence: 92%
“…Other authors have found an increase in UR with higher parity [ 3 , 7 , 9 ]. For example, a study examining risk of complete UR in Norway found women (without a previous cesarean delivery) with a parity of three or more had 2.4 greater odds of complete UR compared to women with less than three births [ 7 ]. Results on the influence of grand multiparity compared to lower parity (2–4 births) on UR from studies in low-income countries are mixed [ 3 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Vaginal delivery is recommended in all but the most unusual cases of stillbirth, where clinical indications exist or because of the preference of the patient [ 12 , 18 ]. Caesarean section is associated with short and long-term maternal morbidity, including an increased possibility of uterine rupture in future induced births [ 44 46 ], and fetal mortality in future pregnancies [ 47 ]. For births ≥ 26 weeks gestation, the study found an overall caesarean rate of 22.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Zirqi et al, in 2016, concluded that a major risk factor for complete uterine rupture in intact and scarred uteri was the sequential labor induction with prostaglandins and oxytocin, compared to spontaneous labor [7]. Other significant risk factors include labor augmentation with oxytocin, antepartum fetal death and previous first-trimester miscarriages [10].…”
Section: Discussionmentioning
confidence: 99%